2017
DOI: 10.1074/jbc.m116.751537
|View full text |Cite
|
Sign up to set email alerts
|

Two Small Molecules Restore Stability to a Subpopulation of the Cystic Fibrosis Transmembrane Conductance Regulator with the Predominant Disease-causing Mutation

Abstract: Cystic fibrosis (CF) is caused by mutations that disrupt the plasma membrane expression, stability, and function of the cystic fibrosis transmembrane conductance regulator (CFTR) Cl− channel. Two small molecules, the CFTR corrector lumacaftor and the potentiator ivacaftor, are now used clinically to treat CF, although some studies suggest that they have counteracting effects on CFTR stability. Here, we investigated the impact of these compounds on the instability of F508del-CFTR, the most common CF mutation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 78 publications
15
73
0
Order By: Relevance
“…The ∆F508 mutation also impairs CFTR assembly (58) partly because of abnormal domain‐domain interactions (1416, 18). CFTR correctors and potentiators may rescue ∆F508‐CFTR defects by targeting some of these abnormalities (23, 25, 59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ∆F508 mutation also impairs CFTR assembly (58) partly because of abnormal domain‐domain interactions (1416, 18). CFTR correctors and potentiators may rescue ∆F508‐CFTR defects by targeting some of these abnormalities (23, 25, 59).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impaired domain‐domain interactions might accelerate ∆F508‐CFTR degradation by the peripheral protein quality control mechanism (5), decrease channel thermostability (23, 24), and reduce open probability ( P o ) (14, 16). Correcting individual structural defects (23, 25) seems to be a promising strategy to restore ∆F508‐CFTR function. However, it is unclear whether loss of function of the F508 residue could account for all abnormalities in ∆F508‐CFTR.…”
mentioning
confidence: 99%
“…It is possible that this combination regiment can benefit patients carrying mutations other than ΔF508 since these two drugs act on two completely different steps for CFTR function. Lately, it was also shown that chronic co-treatment with Lumacaftor plus Ivacaftor restores stability of a small sub-population of ΔF508-CFTR Cl − channels with a majority of the mutants remaining destabilized [51]. A recent study showed that VX-770 acts additively with VX-809 to restore CFTR function in chronically treated R117H/ ΔF508 cells [52].…”
Section: Ongoing Challenges and Future Perspectivesmentioning
confidence: 99%
“…Biochemical and biophysical studies suggest that VX‐809 and VX‐770 interact directly with the hCFTR protein . Molecular docking studies and mutagenesis studies have implicated potential binding sites for VX‐809, yet uncertainty remains, as no direct binding assays have yet been developed.…”
Section: Introductionmentioning
confidence: 99%